2019
DOI: 10.36502/2019/asjbccr.6164
|View full text |Cite
|
Sign up to set email alerts
|

Use of infrared as a complementary treatment approach in medicine and aesthetic medicine

Abstract: Infrared radiation has wavelengths between 780nm and 1000μm. It is well absorbed by living organisms and is perceived as heat. The mechanisms of action of infrared rays on humans are still little known, however their effects on living tissues are well known, particularly useful in the treatment of various diseases and disorders, in the reduction of wound healing times, in weight loss, in non-surgical body remodelling, in photo-rejuvenation, in muscle recovery, in improving sleep quality, in relaxation and in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…While chronic infrared exposure contributes to photo aging [10], the literature suggests a single dose of infrared for up to 48 hours can have a beneficial effect [13]. In one interesting study, a single NIR exposure to human skin was found to increase type I procollagen expression, whereas repeated NIR exposures three times a week for four weeks decreased type I procollagen levels [14].…”
Section: Discussionmentioning
confidence: 99%
“…While chronic infrared exposure contributes to photo aging [10], the literature suggests a single dose of infrared for up to 48 hours can have a beneficial effect [13]. In one interesting study, a single NIR exposure to human skin was found to increase type I procollagen expression, whereas repeated NIR exposures three times a week for four weeks decreased type I procollagen levels [14].…”
Section: Discussionmentioning
confidence: 99%
“…FIR Sauna therapy is quiet promising for chronic pain relief, chronic fatigue syndrome, and weight loss due to neurohormonal cell response (Biro et al, 2003;Masuda et al, 2005a;Masuda et al, 2005b). There are unlimited FIR cosmetic products are available; such as FIR blankets, soft lasers, FIR lamps, FIR caps, and FIR helmets (Cristiano, 2019;Suwandee & Yupapin, 2014). All these tools had medicinal benefits on human cells, both localized and systemic depending upon the tool used.…”
Section: Cosmetics and Aesthetic Medicine And Fir Applicationmentioning
confidence: 99%
“…All these tools had medicinal benefits on human cells, both localized and systemic depending upon the tool used. Removal of fat promotes hair growth and treating alopecia are some of its aesthetic benefits (Cristiano, 2019). The aesthetic FIR devices are also available in markets for home use such as FIR hair brushes to prevent hair loss and hair shining.…”
Section: Cosmetics and Aesthetic Medicine And Fir Applicationmentioning
confidence: 99%
See 2 more Smart Citations